Mars Hill murder (The Wild Rose Press, The Wild Rose Press, Inc., The Wild Rose Press Inc, 2023)
Reporter Miles Harper is on probation at the northern Arizona daily newspaper where he works, because his lack of attention to detail has put him on ice as thin as his notebook pages. His boss wants him out, but gives him one more chance to redeem himself. Maddy Sullivan is new to town, on the run from a violent husband who wants her back. She and Miles meet at a coffee shop, and forge a hesitant friendship. Police Detective Luis Ortega, Miles's former college roommate, just wants to solve crimes. And someone is supplying those crimes by murdering low-level Flagstaff workers. Will these three figure out who the killer is before more people die? Will Miles help solve the mystery, write about it, and save his career? And will Maddy stay safe from the horrid man she once loved?

Camino winds (Camino Island, 02,, 2021)
"Welcome back to Camino Island, where anything can happen - even a murder in the midst of a hurricane, which might prove to be the perfect crime ... Just as Bruce Cable's Bay Books is preparing for the return of bestselling author Mercer Mann, Hurricane Leo veers from its predicted course and heads straight for the island. Florida's governor orders a mandatory evacuation, and most residents board up their houses and flee to the mainland, but Bruce decides to stay and ride out the storm. The hurricane is devastating: homes and condos are leveled, hotels and storefronts ruined, streets flooded, and a dozen people lose their lives. One of the apparent victims is Nelson Kerr, a friend of Bruce's and an author of thrillers. But the nature of Nelson's injuries suggests that the storm wasn't the cause of his death: He has suffered several suspicious blows to the head. Who would want Nelson dead? The local police are overwhelmed in the aftermath of the storm and ill equipped to handle the case. Bruce begins to wonder if the shady characters in Nelson's novels might be more real than fictional. And somewhere on Nelson's computer is the manuscript of his new novel. Could the key to the case be right there - in black and white? As Bruce starts to investigate, what he discovers between the lines is more shocking than any of Nelson's plot twists - and far more dangerous. -- provided by publisher

Deep in the Alaskan woods (The Alaskan Wild, Book 1,, 2021)
"Alexandra Collister came to her estranged cousins' B and B in Falls Lake, Alaska, looking for a fresh start. The surrounding forest can be harsh and unforgiving--luckily, rugged wilderness tracker Quinn Mantell offers to be her guide. Still recovering from a toxic previous relationship, Alex is wary of getting too close, but when savagely deep claw marks appear outside her bedroom window, keeping her distance from Quinn is no longer an option. Then a body turns up exhibiting the same ruthless slash marks, and Alex knows it isn't a coincidence. Something sinister is lurking in the woods around Falls Lake, turning Alex's fresh start into a brutal game of survival. The murky veil of forest offers more threats than answers. Can Alex and Quinn find the killer before darkness falls for good?"--